Paint & ink formulations database - Flick, Ernest W.
This updated database comprises the seminal paint & ink formulations compiled by Ernest Flick and published during the last decade. Extremely valuable to personnel in all facets of paint and ink manufacture and use.
Keywords: Paint -- Databases.; Ink -- Databases.; elektronické knihy; electronic books